PENGARUH SIKAPPEMIMPIN TERHADAP SEMANGAT KERJA PEGAWAI PADA SUKU DINAS PENANGGULANGAN KEBAKARAN DAN PENYELAMATAN KOTAADMINISTRASI JAKARTA PUSAT - Haspian Ruslan; Dimas Andriansyah (Equilibrium Point : Jurnal Manajemen dan Bisnis, 2018)
PThe objectives of this research are: "To find out and analyze the influence of the leader's attitude on the morale of employees at the Central Jakarta City Administration Fire and Rescue Agency".“In this study the author uses quantitative research, because the data obtained will be in the form of numbers. The population in this study were all staff of the Central Jakarta City Administration Fire and Rescue Sub-dept. totaling 48 people. The sampling technique used is by using Simple Random Sampling. By using simple random sampling, a sample of 38 staff at the Central Jakarta City Administration Fire and Rescue Service was taken as respondents in this study.“The results showed that: There was a significant effect of Leader's Attitude (X) on Employee Morale (Y), because the tcount value for the X variable (Leader's Attitude) was 10,648, while the ttable value for N = 38 was 2,024. So 10,648 2,024, it can be concluded that partially the leader's attitude variable (X) has an effect on employee morale (Y). As for the value of R2 (R Square) of 0.759. This shows that 75.9% of the leader's attitude has a positive effect on employee morale while the remaining 24.1% has an effect on other factors not examined in this study. That is, the more precise the attitude of the leadership style that is applied, the morale of the employees of the Central Jakarta City Administration Fire and Rescue Sub-dept. will increase.